MiR-188-5p inhibits cell proliferation and migration in ovarian cancer via competing for CCND2 with ELAVL1: miR-188-5p inhibits ovarian cancer development - Zhang, Hongying; Yuan, Ningxia; Che, Hongcai; Cheng, Xifeng (Cellular and Molecular Biology, 2023)
MicroRNAs (miRNAs) were reportedly demonstrated to participate in ovarian cancer (OC) progression. Here, we inquired into the role of miR-188-5punderneath OC cell proliferation and migration. In this respect, our work examined the miR-188-5p expression and demonstrated its expression level in OC by qRT-PCR analysis. Enforced miR-188-5p expression resulted in a serious downfall of cell growth and mobility, and acceleration apoptosis in OC cells. Furthermore, we identified CCND2 as a target gene of miR-188-5p. RIP assay and luciferase reporter assay verified the interaction of miR-188-5p and CCND2 and exhibited that miR-188-5p greatly hindered the expression of CCND2. Besides, HuR stabilized CCND2 mRNA and counteracted the miR-188-5p suppressive effect on CCND2 mRNA. Functionally, rescue experiments also showed that miR-188-5p-mediated suppression on OC cell proliferation and migration was reverted by CCND2 or HuR overexpression. Our study found miR-188-5p was a tumor suppressor in OC via competing for CCND2 with ELAVL1, contributing to coming up with novel clues for OC therapies.